Piecewise-defined function for effectively implementing the audio volume automation - Lupsa-Tataru, Lucian (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Typically performed with the aid of media development software like digital audio workstations, audio volume automation requires the implementation of piecewise functions to customize the amplitude envelope of audio contents. The user sets various control points by imposing values for the audio volume at different playback positions and, in return, the application shapes the fades to be applied between each two neighboring control points. The adjustable fades, which act over the subintervals defined by each two back-to-back control points, are traditionally implemented by means of labored transcendental functions. In order to effectively construct the envelope of audio contents as well as to heighten the audio experience with a view to real-time computing, we advance a piecewise mapping with the sub-functions, depicting the adjustable fades, represented by rational functions only. A plain implementation in JavaScript is presented in the paper in order to highlight the real-time audio capabilities of the suggested procedure of performing audio volume automation.